2015
DOI: 10.1227/neu.0000000000000969
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation of Heschl Gyrus

Abstract: DBS, deep brain stimulatorEEG, electroencephalographyHG, Heschl gyrus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The second patient had a 30-35% reduction with baseline tinnitus recurring at two-year follow-up. The orientation and depth of Heschl's gyrus within the temporal operculum poses a challenge in optimal and safe placement of a strip electrode within the sylvian fissure (37).…”
Section: Intracranial Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The second patient had a 30-35% reduction with baseline tinnitus recurring at two-year follow-up. The orientation and depth of Heschl's gyrus within the temporal operculum poses a challenge in optimal and safe placement of a strip electrode within the sylvian fissure (37).…”
Section: Intracranial Stimulationmentioning
confidence: 99%
“…This points to a potential modulatory effect from the primary auditory cortex on perception and emotional coding of the percept (38). Donovan et al demonstrated the safety of DBS of Heschl's gyrus in nine patients, although there was no discussion of efficacy (37). The results of the two papers with outcome data show promise, but there are no consistent methods to predict response at this time.…”
Section: Intracranial Stimulationmentioning
confidence: 99%
“…Investigations on this topic are currently not available. Anatomically and surgically, such a targeted implantation of electrodes seems to be possible, if it turned out to be therapeutically reasonable in cases of tinnitus [124]. The German practice guideline on deep brain stimulation, however, does not include the indication of tinnitus [125].…”
Section: Neuromodulation – Instrument-based Medical Interventionsmentioning
confidence: 99%
“…Previous studies have shown that stimulation of the superior temporal gyrus evokes auditory hallucinations (water dripping, buzzing, human voices) (Selimbeyoglu and Parvizi, 2010; 10.3389/fnins.2024.1428256 Leonard et al, 2019). Furthermore, the deep brain stimulation of Heschl's gyrus can evoke the perception of distal tones (Donovan et al, 2015). Recently, studies have shown that electrical stimulation of the planum temporale improves speech perception in noise, which shows applications of brain stimulation in restoring hearing.…”
Section: Introductionmentioning
confidence: 99%